Improving the Compliance of Intraoperative Antibiotic Redosing: A Quality Improvement Initiative - LeRiger, Michelle M. (Pediatr Qual Saf, 2020)
INTRODUCTION: At Children’s Hospital and Medical Center in Omaha, Nebraska, the intraoperative antibiotic redosing guidelines and the time frame considered compliant for redosing were unclear. This lack of clarity plus an ill-defined process for ensuring intraoperative antibiotic redosing resulted in a compliance rate of 11%. The organization’s surgical site infection (SSI) rate was 3.19%, above the national benchmark of 1.87%. The primary project goal was to increase intraoperative antibiotic redosing compliance. The secondary project goal was to decrease SSIs. METHODS: With recommendations from the Infectious Disease Society of America, we developed new organizational redosing guidelines, as well as a new antibiotic-specific reminder alert in the electronic medical record. Implementation of the new guidelines and processes occurred after providing education to the anesthesiologists, surgeons, and circulating nurses. Monthly evaluation of data allowed for quick recognition of oversights followed by the initiation of process updates. RESULTS: Data showed that the initial compliance rate for the intraoperative redosing of antibiotics was 11%. Following interventions, compliance has reached and sustained an average of 99%. Survey results show that provider knowledge of the guidelines and process has improved. Though not directly related, the National Surgical Quality Improvement Program observed that the SSI rate decreased from 3.19% in 2014 to 2.3% in 2018. CONCLUSIONS: This project demonstrates that comprehensive education along with antibiotic-specific electronic medical record alerts significantly increased the compliance of intraoperative antibiotic redosing at Children’s Hospital & Medical Center. Continuous education and monthly updates sustained results for over 40 months.